Database security, IX status and prospects : proceedings of the Ninth Annual IFIP TC11 Working Conference on Database Security, August 1995 - Spooner, David L.; Demurjian, Steven A.; Dobson, John E. (Chapman & Hall on behalf of the International Federation for Information Processing, 1996)
This book documents progress and presents a broad perspective of recent developments in database security. It also discusses in depth the current state-of-the-art in research in the field. A number of topics are explored in detail including: current reseearch in database security and the state of security controls in present commercial database systems. Database Security IX will be essential reading for advanced students working in the area of database security research and development in for industrial researchers in this technical area.